2023
DOI: 10.1161/jaha.122.026763
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Characteristics in a Cohort of Hmong American Patients

Abstract: Background Prior studies have indicated high rates of vascular risk factors, but little is known about stroke in Hmong. Methods and Results The institutional Get With The Guidelines (GWTG) database was used to identify patients discharged with acute ischemic stroke, intracerebral hemorrhage, or subarachnoid hemorrhage between 2010 and 2019. Hmong patients were identified using clan names and primary language. Univariate analysis was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 39 publications
5
1
0
Order By: Relevance
“…Non-white patients with ICH had the youngest median age compared to non-white patients of other stroke subtypes. We also observed that the proportion of ICH was higher in the non-white group, which is consistent with findings in Hmong Americans [20], other Asian ethnicities, such as Japanese [21] and Chinese [22], and Asian Americans in general [23,24]. This means that a larger proportion of younger nonwhite patients suffer from ICH, which is a disease with higher morbidity and mortality [25] and, unlike AIS, has no effective therapeutic intervention [26].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Non-white patients with ICH had the youngest median age compared to non-white patients of other stroke subtypes. We also observed that the proportion of ICH was higher in the non-white group, which is consistent with findings in Hmong Americans [20], other Asian ethnicities, such as Japanese [21] and Chinese [22], and Asian Americans in general [23,24]. This means that a larger proportion of younger nonwhite patients suffer from ICH, which is a disease with higher morbidity and mortality [25] and, unlike AIS, has no effective therapeutic intervention [26].…”
Section: Discussionsupporting
confidence: 88%
“…We observed that the median age of non-white patients was 11 years younger than that of the white patients, which is the same difference observed between Hmong Americans and white patients [20]. Non-white patients with ICH had the youngest median age compared to non-white patients of other stroke subtypes.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations